2019
DOI: 10.1002/mus.26441
|View full text |Cite
|
Sign up to set email alerts
|

Twice‐weekly glucocorticosteroids in infants and young boys with Duchenne muscular dystrophy

Abstract: Introduction: Glucocorticosteroids (GC) are effective in slowing weakness in boys with Duchenne muscular dystrophy (DMD). Methods: This is a multisite, 1‐year, open‐label trial of twice‐weekly prednisolone (5 mg/kg/dose) in infants/young boys (0.4–2.4 years) with DMD. We compared changes in Bayley III Scales of Infant Development (Bayley‐III) with untreated boys followed for 1 year (historical control cohort [HCC]). Twenty‐three of 25 participants completed the study. Results: Treated boys gained an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…The daily GC-treated DMD group showed increased markers of insulin resistance and fat mass without significant changes with BMIs, similar to the weekend GC-treated group. The similar ambulatory function in the weekend GC-and daily CG-treated groups hints that intermittent GC steroids provide comparable benefits but without the same metabolic stress, similar to other patient cohorts; however, this now provides data from longer treatment duration (11,12,38). Ultimately, optimizing GC regimens in dystrophic patients requires further human studies (7); the data presented herein provide some potential serum and body composition measures that could aid in tailoring steroid regimens to maximize benefit while reducing side effects.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The daily GC-treated DMD group showed increased markers of insulin resistance and fat mass without significant changes with BMIs, similar to the weekend GC-treated group. The similar ambulatory function in the weekend GC-and daily CG-treated groups hints that intermittent GC steroids provide comparable benefits but without the same metabolic stress, similar to other patient cohorts; however, this now provides data from longer treatment duration (11,12,38). Ultimately, optimizing GC regimens in dystrophic patients requires further human studies (7); the data presented herein provide some potential serum and body composition measures that could aid in tailoring steroid regimens to maximize benefit while reducing side effects.…”
Section: Discussionmentioning
confidence: 72%
“…In dysferlin-deficient muscular dystrophy, a randomized study of deflazacort in 25 patients for 6 months showed a trend toward worsening muscle function and steroid-induced side effects compared with placebo (10). Alternative GC dosing strategies have been suggested to limit side effects (11,12), but the clinical benefit of these strategies are debated. Recently, we compared daily GC steroids to an intermittent once-weekly (pulsatile) GC steroid protocol for the ability to promote muscle repair in dystrophic mice (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Connolly et al demonstrated that this intermittent dosing regimen did not affect the linear growth of these young boys, nor was it associated with a change in average heart rate or blood pressure. 18 Overall, the boys were not reported to exhibit an increased risk of nonmanageable side effects, including irritability, sleep difficulty, or cushingoid features. Biochemical testing revealed no hyperglycemia, and bone mineral density measurements improved over the 12 months of intermittent GC dosing.…”
mentioning
confidence: 90%
“…The study by Connolly et al . in this issue examines the use of intermittent twice‐weekly or “weekend” GC therapy for infants and young boys (3–30 months old) with DMD.…”
mentioning
confidence: 99%
See 1 more Smart Citation